2021
DOI: 10.3389/fphys.2021.670989
|View full text |Cite
|
Sign up to set email alerts
|

Strenuous Physical Training, Physical Fitness, Body Composition and Bacteroides to Prevotella Ratio in the Gut of Elderly Athletes

Abstract: Regular physical activity seems to have a positive effect on the microbiota composition of the elderly, but little is known about the added possible benefits of strenuous endurance training. To gain insight into the physiology of the elderly and to identify biomarkers associated with endurance training, we combined different omics approaches. We aimed to investigate the gut microbiome, plasma composition, body composition, cardiorespiratory fitness, and muscle strength of lifetime elderly endurance athletes (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 56 publications
(72 reference statements)
2
42
1
3
Order By: Relevance
“…Because Akkermansia muciniphila is the only known species of this phylum, the difference was further quantified with PCR, which confirmed that A. muciniphila was more abundant in the physically active than inactive women [30]. In another cross-sectional study, Verrucomicrobia was also shown to be more abundant in elderly men with lifelong training background compared with controls [31]. It is not known how a physically active lifestyle would increase the abundance of Akkermansia, but it could be that the dietary habits of the active individuals play a role.…”
Section: Cross-sectional Studies Have Reported Associations Between Exercise Physical Performance and The Gut Microbiota In Humans-some Ementioning
confidence: 78%
See 4 more Smart Citations
“…Because Akkermansia muciniphila is the only known species of this phylum, the difference was further quantified with PCR, which confirmed that A. muciniphila was more abundant in the physically active than inactive women [30]. In another cross-sectional study, Verrucomicrobia was also shown to be more abundant in elderly men with lifelong training background compared with controls [31]. It is not known how a physically active lifestyle would increase the abundance of Akkermansia, but it could be that the dietary habits of the active individuals play a role.…”
Section: Cross-sectional Studies Have Reported Associations Between Exercise Physical Performance and The Gut Microbiota In Humans-some Ementioning
confidence: 78%
“…The sole known species of the Faecalibacterium genus, Faecalibacterium prausnitzii is one of the most abundant commensals with important antiinflammatory functions [61][62][63], and we have shown that this health-beneficial bacterium can ameliorate non-alcoholic fatty liver disease, too [64]. The abundance of F. prausnitzii has been shown to be higher in elite endurance runner women [38] and in healthy, physically active, premenopausal women than in sedentary counterparts [30], although the situation was contrary among active elderly men [31]. However, it seems that exercise may increase the abundance of Faecalibacterium and whether the increased abundance of this anti-inflammatory bacterium could be related to some of the anti-inflammatory effects of exercise (e.g., [65]), should be studied in the future.…”
Section: Endurance Exercise and Gut Microbiotamentioning
confidence: 89%
See 3 more Smart Citations